ANALISIS PENGARUH DIRECT MARKETING DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA DS GALLERY - Nur Halima Halim; Siske Tontong (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the effect of direct marketing and digital marketing on consumer purchasing decisions at DS Gallery. The research method used is an associative method with a quantitative approach. Data collection techniques were carried out through the distribution of questionnaires to respondents, which were then analyzed using multiple linear regression with the assistance of SPSS software. The results of the study indicate that direct marketing has a positive and significant effect on purchasing decisions. Similarly, digital marketing also shows a positive and significant influence. These findings suggest that both direct marketing and digital marketing strategies need to be continuously optimized to enhance consumers' purchasing power toward DS Gallery products.